Emerging Temporal Lobe Dysfunction in People at Clinical High Risk for Psychosis - Allen, Paul; Moore, Holly; Corcoran, Cheryl M.; Gilleen, James; Kozhuharova, Petya; Reichenberg, Avi; Malaspina, Dolores (Frontiers in Psychiatry, 2019)
Clinical high-risk (CHR) individuals have been increasingly utilised to investigate the prodromal phases of psychosis and progression to illness. Research has identified medial and lateral temporal lobe abnormalities in CHR individuals. Dysfunction in the medial temporal lobe, particularly the hippocampus, is linked to dysregulation of glutamate and dopamine via a hippocampal-striatal-midbrain network that may lead to aberrant signalling of salience underpinning the formation of delusions. Similarly, lateral temporal dysfunction may be linked to the disorganised speech and language impairments observed in the CHR stage. Here we summarise the significance of these neurobiological findings in terms of emergent psychotic symptoms and conversion to psychosis in CHR populations. We propose key questions for future work with the aim to identify the neural mechanisms that underlie the development of psychosis.